Mechanism of Qingchang Suppository on repairing the intestinal mucosal barrier in ulcerative colitis - Shan, Jingyi; Liu, Suxian; Liu, Haoyue; Yuan, Jianye; Lin, Jiang (Frontiers in Pharmacology, 2023)
Ulcerative colitis (UC) is a refractory inflammatory bowel disease, and the outcomes of conventional therapies of UC, including 5-aminosalicylic acid, glucocorticoids, immunosuppressants, and biological agents, are not satisfied with patients and physicians with regard to adverse reactions and financial burden. The abnormality of the intestinal mucosal barrier in the pathogenesis of UC was verified. Qingchang Suppository (QCS) is an herbal preparation and is effective in treating ulcerative proctitis. The mechanism of QCS and its active ingredients have not been concluded especially in mucosal healing. This review elucidated the potential mechanism of QCS from the intestinal mucosal barrier perspective to help exploring future QCS research directions.